ANALISA DESKRIPTIF PENGELOMPOKAN DATA KONSENTRASI PM2,5 BERDASARKAN HARI PADA TITIK PEMANTAUAN BUNDARAN HI JAKARTA UNTUK DATA FEBRUARI-OKTOBER 2021 - Nelvidawati Nelvidawati (JICE (Journal of Infrastructural in Civil Engineering), 2022)
The very high flow of vehicles passing through Bundaran HI has resulted in a decrease in air quality in this area. PM2,5 is one of the pollutant substances produced from vehicle fumes that can be harmful to health. The number of vehicles that pass through this area depends on the presence of office and business activities. The purpose of this study was to determine the pattern of distribution of PM2.5 concentration data by day and how much data did not exceed the quality standard. The research was conducted by descriptive method. The results showed that the pattern of distribution of PM2.5 data which was below the quality standard occurred in February to mid-April 2021 and early June to early July. This is due to the PSBB and PPKM that apply in the city of Jakarta. When the regulation was revoked, the concentration of PM2.5 was more dominant above the quality standard. If the data is grouped by day, the percentage of PM2.5 concentration data that does not pass the quality standard is Monday 43.59%, Tuesday 35.89%, Wednesday 38.46%, Thursday 41.02%, Friday 41.03%, Saturday 56 .41%, Sunday 41.02%..